School curricullum and enviromental sustainability - Kariuki, Scolastica; Boyo, Barnard; Bowen, Michael; Kiambi, Purity (Technium Social Sciences Journal, 2022)
Despite far-reaching environmental concerns, school curriculum in Kenya lacks adequate environmental sustainability address, yet global indicators show deterioration of the environment in developing countries is obviously leading to loss of biodiversity, rise in carbon levels, climate change (UNESCO. 2016) and overall poor-quality life. Research conducted on values education and environmental sustainability determined effective approaches to promote environment sustainability among school going children in Kenya. Inadequate environmental values education was hypothesized to lead to low awareness and action towards sustainability. To determine the extent to which Kenya’s education curriculum addresses environmental sustainability values for ESD, the findings form a basis for proposing innovation in EESD in school curricular. Mixed research design involved content analysis of the curricula and textbooks, descriptive surveys and expert interviews. Multistage sampling was applied among students and teachers from 8 former provinces of Kenya for administration of questionnaires to determine environmental content in educational materials, values and skills taught. Expert officials from KICD, MOEST, and UNEP were selected using purposive sampling for interviewing on required content, policy and adequacy. Findings indicated that EESD is not explicitly taught, does not adequately reflect in curricular objectives or textbooks, teaching on environment is mainly knowledge based and lacks experiential learning activities, heads of department (50%) have no training on environmental issues, students (51.8%) have not learnt enough of environmental issues, teachers (56%) are not motivated to teach about environment, and over 62% of teachers report the curriculum is insufficient to develop environmental values. MoE and NEEMA confirmed that values and policy on environmental sustainability are insufficiently taught, teachers are inadequately trained and initiatives on curriculum for environmental sustainability are inconclusive. Teaching and learning for EESD in Kenya is based on inadequate content, values and methodology. In conclusion appropriate EESD content, values and methodologies should be integrated in unfolding curriculum reviews for school. Key Words: School Curricular Environmental Education Environmental Education for Sustainable Development Environmental Sustainabilit